2013
DOI: 10.1097/aog.0b013e318299a6cf
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Trends in the Performance of Inpatient Hysterectomy in the United States

Abstract: OBJECTIVE To examine the use of inpatient hysterectomy and explore changes in the use of various routes of hysterectomy and patterns of referral. METHODS The Nationwide Inpatient Sample was used to identify all women aged 18 years or older who underwent inpatient hysterectomy between 1998 and 2010. Weighted estimates of national trends were calculated and the number of procedures performed estimated. Trends in hospital volume and across hospital characteristics were examined. RESULTS After weighting, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
433
0
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 637 publications
(468 citation statements)
references
References 31 publications
19
433
0
16
Order By: Relevance
“…1 Despite several minimally invasive techniques now available, including Total Vaginal Hysterectomy (TVH) and Laparoscopic Hysterectomy (LH) approaches, the vast majority are still performed with a laparotomy or via the Abdominal Hysterectomy (AH). [1][2][3] It has been reported that over two thirds of hysterectomies continue to be performed in the United States as open abdominal procedures, with the lowest rates in the Southern region.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Despite several minimally invasive techniques now available, including Total Vaginal Hysterectomy (TVH) and Laparoscopic Hysterectomy (LH) approaches, the vast majority are still performed with a laparotomy or via the Abdominal Hysterectomy (AH). [1][2][3] It has been reported that over two thirds of hysterectomies continue to be performed in the United States as open abdominal procedures, with the lowest rates in the Southern region.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite several minimally invasive techniques now available, including Total Vaginal Hysterectomy (TVH) and Laparoscopic Hysterectomy (LH) approaches, the vast majority are still performed with a laparotomy or via the Abdominal Hysterectomy (AH). [1][2][3] It has been reported that over two thirds of hysterectomies continue to be performed in the United States as open abdominal procedures, with the lowest rates in the Southern region. [1][2][3][4] It has been well established that minimally invasive techniques, both laparoscopic and vaginal hysterectomy, have distinct advantages over abdominal approaches, including decreased length of hospitalization, reduced postoperative infections, shorter recovery times, and decreased blood loss.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…
It is estimated that one in three women undergo hysterectomy in the USA, with the majority of these procedures performed via open abdominal surgery [1]. It is well known that morbidity related to hysterectomy can be reduced by using less invasive surgical techniques, such as vaginal and laparoscopic approaches.
…”
mentioning
confidence: 99%